The Cruise Port Place Selection Problem with Extended VIKOR and ANP Methodologies under Fuzzy Environment - Demirel, Nihan Cetin; Yucenur, G. Nilay (INT ASSOC ENGINEERS-IAENG, 2011)
In this paper, a decision making problem is considered and fuzzy analytic network process (ANP) and extended fuzzy VIKOR methodologies have been proposed to deal with the cruise port place selection problem in Istanbul. In this paper, we proposed a model for selection of the most suitable place by using analytical network process and VIKOR method under fuzzy environment due to linguistic terms. The implementation of the system is demonstrated by a problem having four stages of hierarchy which contains four criteria and thirteen sub-criteria. The study compares the fuzzy analytic network process and VIKOR method results.
Keywords: Multi-criteria decision making problem; Fuzzy ANP; extended VIKOR method; cruise port; DECISION-MAKING; Computer Science; Engineering